How to create patients revisit intention? A study on private hospitals in Indonesia - Tantri Yanuar Rahmat Syah; Edi Suyitno (Innovative Marketing, 2025)
This study investigates the factors influencing the revisit intentions of female diabetes patients at private hospitals in Indonesia. The research explores the roles of complaint handling and social media promotion in building patient trust and satisfaction, and their impact on the intention to return. Utilizing a quantitative approach with a survey of 131 respondents, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among the factors. The findings reveal that while service quality significantly affects patient satisfaction, it does not directly influence revisit intentions. Effective complaint handling enhances patient trust, particularly for those with more complex diabetes cases, and social media promotion positively impacts both trust and revisit intentions. The implications of these findings suggest that hospitals should focus on improving operational efficiency, handling complaints effectively, and implementing robust social media strategies to strengthen patient loyalty and retention. This research provides valuable insights for healthcare providers aiming to boost patient satisfaction and revisit rates amidst competitive and resource-limited environments.